Surgical management of acute claw hand in a competitive baseball player - McDonald, L. S.; Degen, R. M.; Altchek, D. W. (The Physician and Sportsmedicine, 2017)
We describe an unusual case of acute ulnar neuropathy with a flexible claw hand deformity in a baseball pitcher. Treatment involved ulnar nerve decompression at the elbow with subsequent recurrence of symptoms upon return to pitching. Definitive treatment included a wide secondary release of tethered locations resulting in return of function. At final follow-up the patient has returned to unrestricted baseball throwing activities.